(untitled) (KULT_online, 2024)
The volume One-Track Mind: Capitalism, Technology, and the Art of the Pop Song, edited by historian Asif Siddiqi, brings together 16 essays by scholars of history, media studies, musicology and music journalists, each of which tell the (fragmented) history of popular music from the 1960s to the 2010s. Using the song as a lens, the essays illuminate both the political agency of songs and the contexts that shape them.